A Comprehensive Review of the Therapeutic Value of Urine-Derived Stem Cells - Zhou, Qian; Cheng, Yiyu; Sun, Fang; Shen, Jie; Nasser, M. I.; Zhu, Ping; Zhang, Xueyan; Li, Yuxiang; Yin, Guangming; Wang, Yuequn; Wu, Xiushan; Zhao, Mingyi (Frontiers in Genetics, 2022)
Stem cells possess regenerative powers and multidirectional differentiation potential and play an important role in disease treatment and basic medical research. Urine-derived stem cells (USCs) represent a newly discovered type of stem cell with biological characteristics similar to those of mesenchymal stromal cells (MSCs), including their doubling time and immunophenotype. USCs are noninvasive and can be readily obtained from voided urine and steadily cultured. Based on advances in this field, USCs and their secretions have increasingly emerged as ideal sources. USCs may play regulatory roles in the cellular immune system, oxidative stress, revascularization, apoptosis and autophagy. This review summarizes the applications of USCs in tissue regeneration and various disease treatments. Furthermore, by analysing their limitations, we anticipate the development of more feasible therapeutic strategies to promote USC-based individualized treatment.